(untitled) (Comparatismi, 2022)
This paper aims to improve knowledge regarding the use of narrative texts in the treatment of people with trauma and suffering from PTSD. To achieve this goal, results from narrative persuasion studies, with reference to research on transportation (involvement with the storyline: feeling of being lost in the story) and identification (allegiance with characters) were used. This paper proposes the results of two experimental studies. The main objective of both studies was to increase the knowledge concerning narrative prototypes that have turned out to be effective in the treatment of people afflicted with traumatic and post-traumatic syndrome. The first study analyzes the role played by the narrative reconstruction of traumatic events by traumatized subjects as a tool for reducing stress levels and provides an analysis of the narrative and linguistic structures used in the narrative reconstruction of traumatic events. The second study, on the other hand, examines above all the role of reading narrative texts as a tool to mitigate stress levels and tries to establish what role perceived realism and the type of narrator play on the narrative transport of readers.